Technical efficiency of automobiles: A nonparametric approach incorporating carbon dioxide emissions - Benjamin Hampf; Jens J. Krüger (Technische Universität Darmstadt, Department of Law and Economics, 2010)
We conduct an empirical analysis of the technical efficiency of cars sold in Germany in 2010. The analysis is performed using traditional data envelopment analysis (DEA) as well as directional distance functions (DDF). The approach of DDF allows incorporating the reduction of carbon dioxide emissions as an environmental goal in the efficiency analysis. A frontier separation approach is used to gain deeper insight for different car classes and regions of origin. Natural gas driven cars and sports-utility-vehicles are also treated as different groups. The results show that the efficiency measurement is significantly influenced by the incorporation of carbon dioxide emissions. Moreover, we find that there is indeed a trade-off between technological performance and environmental performance.
Keywords: C14; L62; Q53; 330; nonparametric efficiency measurement; directional distance function; automobiles; air pollution; Personenkraftwagen; Kraftfahrzeug; Technische Effizienz; Kohlendioxid; Umweltbelastung; Schätzung; Deutschland